Adsorption thermodynamics and isosteric heat of adsorption of toxic metal ions onto bagasse fly ash (BFA) and rice husk ash (RHA) - Srivastava V.C.; Mall I.D.; Mishra I.M. (My University, 2025)
The equilibrium sorption characteristics of cadmium (Cd(II)), nickel (Ni(II)) and zinc (Zn(II)) metal ions from aqueous solutions having respective metal ion concentrations in the range of 50-500 mmol/dm3 for two low-cost adsorbents, viz. bagasse fly ash (BFA) and rice husk ash (RHA), were studied at different temperatures in the range of 293-323 K. An increase in temperature is found to induce a positive effect on the sorption process. Toth isotherm best represents the equilibrium adsorption onto BFA and RHA. The heat of adsorption (ΔH0) and change in entropy (ΔS0) for metal adsorption on BFA and RHA are found in the range of 26-44 kJ/mol and 127-194 kJ/mol K, respectively. The isosteric heat of adsorption was quantitatively correlated with the fractional loading of metal ions onto adsorbents. The results showed that the BFA and RHA possessed heterogeneous surface with sorption sites having different activities. © 2007 Elsevier B.V. All rights reserved.